Articulated motion and deformable objects : 9th international conference, AMDO 2016, Palma de Mallorca, Spain, July 13-15, 2016, proceedings /: 9th international conference, AMDO 2016, Palma de Mallorca, Spain, July 13-15, 2016, proceedings. (2016) - Unknown
No abstract available